Leptin u pacientů s nefrotickým syndromem - Merta, M; Rysavá, R; Ríhová, Z; Kmentová, D; Remes, O; Tesar, V (Sbornik lekarsky, 2003)
Nephrotic syndrome (NS) remains a serious clinical setting characterized by marked proteinuria, hypoproteinemia and hypercholesterolemia, usually accompanied by the presence of oedemas. It could be presumed, that the newly discovered hormone leptin plays an important role in the complex metabolic processes occurring in patients with NS, in which apart from the changes in the hydratation, and the protein and lipid spectre profile changes, the alteration of the metabolism of glycides elicited by the treatment with corticosteroids (CS) is often observed. The aim of the study was to investigate the plasma levels of leptin and its plasma soluble receptor (sLe-R) before and after the treatment with CS and to evaluate their relationship with albuminemia and/or proteinuria. The study group consisted of 15 men and 15 women (mean age 49 +/- 13.7 years) with newly diagnosed NS, verified by renal biopsy, in which subsequently CS treatment was started. Before the treatment (period 1) and further one month (period 2) and six months (period 3) after the start of the treatment the following parameters were measured: body mass index (BMI), serum levels of creatinine, albumin, cholesterol, triglyceride, cholinesterase, proteinuria/24 hour and plasma levels of leptin and sLe-R. In comparison to the relatively high values of BMI in the period 1 a decrease of BMI towards the physiologic range was observed during the treatment periods. Statistically significant changes were also observed in proteinuria (decrease) and in serum cholesterol and albumin levels of whereas in other biochemical parameters, including plasma leptin and sLe-R levels, statistically significant changes were not found. A trend to negative correlation with borderline statistical significance could be observed between leptin and sLe-R. The results of our relatively unique study on leptin--dealing with long-term follow-up of the patients with NS suggest that regardless prominent metabolic alterations present in NS the plasma levels of leptin and sLe-R remain relatively stable, and that of regulation of leptin in this setting is probably complex and multifactorial.
Keywords: nefrotický syndrom; leptin; Male; Nephrotic Syndrome; Adolescent; sérový albumin; Receptors, Leptin; Adult; Aged; dospělí; mužské pohlaví; senioři; receptory buněčného povrchu; leptinové receptory; Serum Albumin; mladiství; Glucocorticoids; proteinurie; lidé; glukokortikoidy; ženské pohlaví; Humans; Receptors, Cell Surface; Proteinuria; Female; lidé středního věku; Leptin; Middle Aged